(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
Shale samples from the volcaniclastic turbidites ascribed to the Tusa Tuffite Formation (Tufiti di Tusa Auct.) cropping out at the Canale Candela section (Calabro-Lucano boundary, southern Italy) have yielded rich, diverse and well-preserved palynomorph and calcareous nannofossil assemblages. They allow the consistent recognition of both dinoflagellate cyst and calcareous nannofossil zones previously defined in bio- and magnetostratigraphically well calibrated pelagic sequences from the central and northern Apennines. Thus they give the Canale Candela section a first order correlation to the standard chronostratigraphic scale with high precision. On this basis, an earliest Oligocene age is assigned to this succession.Poorly preserved sparse palynological and calcareous nannofossil assemblages have been recovered from the Tusa Tuffite at the type-locality (Nebrodi Mountains, NE Sicily). Hence, no biozonation is proposed for the Tusa section. The overall composition of the Tusa assemblages, however, unequivocally supports the correlation with the Canale Candela volcaniclastic turbidites.The detailed age assessment of the Tusa Tuffite outcrops investigated, as well as facies similarities, give a broad regional correlation with other Rupelian volcaniclastic successions of the Alps/Apennines system, namely the Aveto Formation belonging to the Subligurian Domain of the northern Apennines, the Ranzano Formation belonging to the Epiligurian succession of the northern Apennines and the Taveyanne Sandstones of the western Alps. In this framework, we suggest that a single regional event of rise and erosion of a volcanic arc occurred in the Alps/Apennines orogenic system during the Early Oligocene.